Pelaksanaan Akad Pembiayaan Mudharabah Pada BMT Dana Akhirat Arjasari Kabupaten Bandung - Abdul Hakim; Atshilla Rahmawati Alhamid; Dandan Irawan (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2022)
Mudharabah financing is a revenue sharing system and operational unit of Shari'ah Financial Institution. But the problem that arises is the application of mudharabah financing that is different and not in accordance with the perspective of DSN MUI Fatwa Number: 07/DSN-MUI/IV/2000. This study uses case study method with descriptive data analysis using qualitative approach where data is obtained through informants and documents with data collection techniques through interviews, observations, and library studies. The results of this study show that there are three different provisions with the perspective of the FATWA DSN MUI Number: 07/DSN-MUI/IV/2000 differences in the provisions of mudharabah financing in the KBMT of Dana Akhirat consists of: First in the financing provisions, the distribution of mudharabah financing that should be used for business but there are still many members who do not use the financing for business, so it is not productive. In the financing provisions, KBMT of Dana Akhirat cannot bear the full losses because the provisions at KBMT Dana Akhirat are not to bear losses on the distribution of funds but have been determined at the beginning of the agreement at the time of the agreement.